Knowledge sharing barriers in software development teams: a multiple case study in Turkey - Akgun, Ali E.; Keskin, Halit; Ayar, Hayat; Okunakol, Zeki (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - Changing customer demands, needs and desires; emerging technologies; and increasing competition among firms force software development teams to develop and then implement new software projects to satisfy their customers and become more competitive in their marketplace. In this respect, knowledge sharing is critical for project success. However, although knowledge sharing among team members has been investigated by many researchers, knowledge sharing barriers among people have rarely been addressed in project teams in general and software development teams in particular. Thus, the purpose of this study is to investigate knowledge sharing barriers in the software development team context and develop solutions that can overcome these barriers. Design/methodology/approach - An exploratory multiple case design was used to explore why software team members in Turkey may be reluctant to share knowledge. In this study, the authors conducted 18 in-depth and on-site semi-structured interviews and then employed content analysis, which uses a set of procedures to make valid inferences from text, to discover knowledge sharing barriers. Findings - By interviewing 18 Turkish project team managers, the authors identified knowledge-, individual- and organization-related knowledge sharing barriers among team members. They also demonstrated solutions for the knowledge sharing hesitation among team members based on the experiences of project team managers. Research limitations/implications - Some methodological limitations exist in this study. Specifically, the generalizability of the sampling limits the study, which was conducted in a specific national context, Turkish firms in general and the Istanbul district in particular. It is important to note that readers should be cautious when generalizing the results to different cultural contexts. In this regard, a Turkish sample involving the Istanbul district, like that of any culturally bound research, imposes some constraints on the interpretation and application of the results. The study was conducted with in-depth interviews of only 18 managers working in seven companies. Also, this study was performed on system development teams. The results should be confirmed with more samples and different project sets. Practical implications - In this study, the authors discover the reasons for knowledge sharing reluctance among team members and some solutions that will eliminate knowledge sharing problems by using case studies. The results show that the reluctance of team members arises from obstacles, which are knowledge-, individual- and organization- related. Also, the conclusions demonstrate that knowledge sharing barriers can be resolved by establishing project leadership, creating a knowledge sharing culture and considering team members' emotions. Originality/value - The present study investigated whether reluctance to share knowledge derives not only from individual barriers but also from organization- and knowledge-related barriers in a project team context. The authors discovered that knowledge sharing barriers can be resolved by establishing project leadership, creating a knowledge sharing culture and considering team members' emotions.
Keywords: Project teams; Customer satisfaction; Knowledge management; Knowledge sharing; Software development; PSYCHOLOGICAL OWNERSHIP; PROJECT SUCCESS; INFORMATION; MANAGEMENT; LEADERSHIP; BEHAVIOR; QUALITY; MODEL; Computer Science